KAJIAN INTERAKSI GENOTIPE Ã LINGKUNGAN HASIL KLON-KLON UBI KAYU - , KARTIKA NOERWIJATI ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Multi-environment trials were conducted to analyze the yield potential and to assess the yield stability across environments. The purposes of the study are (1) to obtain information on the G Ã E interactions of fifteen cassava genotypes across five environments, (2) to obtain a more precise model from the utilization of the mixed model of AMMI and GGE techniques using least squares (LS) method and Restricted Maximum Likelihood (REML) method without and with the coefficient of coancentry matrix in G Ã E interactions analysis using both homogeneous and heterogeneous residual error variance assumption across environments, (3) to select cassava clones with a capacity for high yield and broad adaptability or cassava clones with a capacity cassava clones for high yield and specific adaptability as a new cassava variety. The study was conducted at five locations (Kediri, Ponorogo, Probolinggo, Malang, and Mojokerto) from November 2010 to August 2011, using a randomized complete block design with three replications. Materials used in this study were 15 cassava genotypes, consisting of 11 clones which are CMM 03025-43, CMM 03036-7, CMM 03036-5, CMM 03038-7, CMM 03094-12, CMM 03094-4, CMM 03095-5, CMM 02040-1, CMM 02033-1, CMM 02035-3, CMM 02048-6, and four superior cassava cultivars as controls involving Adira 4, UJ 5, Malang 4, and Malang 6. Most of the clones were genetically related. Data were analyzed using combined analysis of variance. Estimation of the value of environmental component (ej), genotype (gi), G Ã E interaction (geij), and the value of G + GE (gi + geij) was performed using the least squares (LS) method (only on homogeneous residual error variance across environments) and the Restricted Maximum Likelihood (REML) method without and with the coefficient of coancestry matrix (using homogeneous and heterogeneous residual error variance across environments). The estimated value of geij were then used for stability analysis using AMMI technique, while the estimated value of gi + geij were used for stability analysis using GGE technique. The combined analysis of variance with the LS method, the REML method without and with A matrix assuming homogeneous residual error variance across environments, as well as the REML method without and with the coefficient of coancentry matrix assuming heterogeneous residual error variance across environments showed G Ã E interactions on tuber yield. Based on the biplot graph formed, GGE is a more effective technique to classify the selection environment than the AMMI technique. The GGE technique by the REML method without the coefficient of coancentry matrix assuming heterogeneous residual error variance across environments is a more precise model. CMMM 03038-7 (G8) has a broad adaptability and high yield potential, and the genotype is the closest to the ideal genotype criteria than other genotypes. CMM 03094-4 (G10) has specific adaptability in Ponorogo (S2) and Mojokerto (S5), and the yield potential higher than that of the control varieties UJ5 (G1), Malang 6 (G2), and Adira 4 (G4). Kediri (S1) has the highest yield among other environments and it is a suitable environment for growth and selection of cassava.